Examining the symbolism of the Ascension (Mi‘rāj): relationships between traditional Malay prose narratives (Ḥikāyāt) and Traditional Malay Mosques in Melaka - Hazwan Ariff Hakimi; Nik Lukman Nik Ibrahim; Nor Zalina Harun (Penerbit Universiti Kebangsaan Malaysia, 2023)
The saying that the Islāmic ritual prayer (ṣalāh) epitomises the ascension (mi‘rāj) of the believer has prompted some scholars to interpret the Prophet Muḥammad’s Ascension (Mi‘rāj) in the traditional mosque’s symbolism in the Islāmic world, including those in Melaka. Despite being original in the Traditionalist sense of the word, their allusions to the symbolism remain methodologically deficient and conceptually limited. Given these circumstances, this article examines the symbolism of the Mi‘rāj in the traditional Malay mosques in Melaka through the traditional Malay prose narratives (ḥikāyāt) which manifest the symbolism of the same. It employs a hermeneutic reading of MSS 2968 Risālat Laṭīfat fī Bayān al-Isrā’ wa-al-Mi‘rāj (1767), the earliest known manuscript narrating the story of Prophet Muḥammad’s Mi‘rāj in the Malay world as well as case studies of three significant and contemporaneous Malay mosques in Melaka, namely Masjid Tengkera (1728), Masjid Kampung Hulu (1728), and Masjid Kampung Kling (1748). By capitalising on the combination of textual, document, and comparative analyses, it was found that there is a correlation between the text and the buildings, in which the symbolism of the Mi‘rāj is manifested in several external and internal architectural elements of all three mosques. These findings present the unity of the traditional Malay-Islāmic heritage generally and the productive relationship between literature and architecture particularly through a provisional methodological and conceptual framework which endeavours to establish the basis for future research on the subject.